B-Cell NHL Subtype Risk Associated with Autoimmune Conditions and PRS - Wang, Sophia S; Vajdic, Claire M; Linet, Martha S; Slager, Susan L; Voutsinas, Jenna; Nieters, Alexandra; Casabonne, Delphine; Cerhan, James R; Cozen, Wendy; Alarcón, Graciela; Martínez-Maza, Otoniel; Brown, Elizabeth E; et al. (Cancer epidemiology, biomarkers & prevention, 2022)
BACKGROUND: A previous International Lymphoma Epidemiology (InterLymph) Consortium evaluation of joint associations between five immune gene variants and autoimmune conditions reported interactions between B-cell response-mediated autoimmune conditions and the rs1800629 genotype on risk of B-cell non-Hodgkin lymphoma (NHL) subtypes. Here, we extend that evaluation using NHL subtype-specific polygenic risk scores (PRS) constructed from loci identified in genome-wide association studies of three common B-cell NHL subtypes. METHODS: In a pooled analysis of NHL cases and controls of Caucasian descent from 14 participating InterLymph studies, we evaluated joint associations between B-cell-mediated autoimmune conditions and tertile (T) of PRS for risk of diffuse large B-cell lymphoma (DLBCL; n = 1,914), follicular lymphoma (n = 1,733), and marginal zone lymphoma (MZL; n = 407), using unconditional logistic regression. RESULTS: We demonstrated a positive association of DLBCL PRS with DLBCL risk [T2 vs. T1: OR = 1.24; 95% confidence interval (CI), 1.08-1.43; T3 vs. T1: OR = 1.81; 95% CI, 1.59-2.07; P-trend (Ptrend) < 0.0001]. DLBCL risk also increased with increasing PRS tertile among those with an autoimmune condition, being highest for those with a B-cell-mediated autoimmune condition and a T3 PRS [OR = 6.46 vs. no autoimmune condition and a T1 PRS, Ptrend < 0.0001, P-interaction (Pinteraction) = 0.49]. Follicular lymphoma and MZL risk demonstrated no evidence of joint associations or significant Pinteraction. CONCLUSIONS: Our results suggest that PRS constructed from currently known subtype-specific loci may not necessarily capture biological pathways shared with autoimmune conditions. IMPACT: Targeted genetic (PRS) screening among population subsets with autoimmune conditions may offer opportunities for identifying those at highest risk for (and early detection from) DLBCL.
Keywords: Lymphoma, Large B-Cell, Diffuse; B-lymfocyty; autoimunitní nemoci; folikulární lymfom; lidé; Lymphoma, Follicular; Genome-Wide Association Study; Case-Control Studies; B-Lymphocytes; difúzní velkobuněčný B-lymfom; studie případů a kontrol; Autoimmune Diseases; celogenomová asociační studie; Humans